2022
DOI: 10.1002/cncr.34368
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health insurance coverage on racial/ethnic disparities in US childhood and adolescent cancer stage at diagnosis

Abstract: Background Racial/ethnic minority children and adolescents are more likely to have an advanced cancer diagnosis compared with non‐Hispanic Whites, which may relate to the lack of consistent health care access. This study aims to describe racial/ethnic disparities in cancer diagnosis stage among children and adolescents and assess whether health insurance mediates these disparities. Methods Data on individuals ≤19 years of age diagnosed with primary cancers from 2007 to 2016 were obtained from the Surveillance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…104 Five-year relative cancer survival is lower among Black people (67%) than among White people (72%) even when socioeconomic status is high, 130 and Black children are 24% more likely to be diagnosed with distant-stage childhood cancer than White children, regardless of family insurance status. 140 The economic burden of racial and ethnic health inequalities was recently estimated at $421-$451 billion in 2018, mostly because of the poor health of Black individuals. 141…”
Section: Cancer Disparities By Race and Ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…104 Five-year relative cancer survival is lower among Black people (67%) than among White people (72%) even when socioeconomic status is high, 130 and Black children are 24% more likely to be diagnosed with distant-stage childhood cancer than White children, regardless of family insurance status. 140 The economic burden of racial and ethnic health inequalities was recently estimated at $421-$451 billion in 2018, mostly because of the poor health of Black individuals. 141…”
Section: Cancer Disparities By Race and Ethnicitymentioning
confidence: 99%
“…In addition, Asian, Black, and Hispanic people are less likely to receive recommended germline genetic testing necessary for the receipt of game‐changing treatments, 139 such as the immunotherapy that has been shown to extend progression‐free 24‐month survival by three‐fold for patients with advanced mismatch‐repair–deficient endometrial cancer 104 . Five‐year relative cancer survival is lower among Black people (67%) than among White people (72%) even when socioeconomic status is high, 130 and Black children are 24% more likely to be diagnosed with distant‐stage childhood cancer than White children, regardless of family insurance status 140 . The economic burden of racial and ethnic health inequalities was recently estimated at $421–$451 billion in 2018, mostly because of the poor health of Black individuals 141 …”
Section: Selected Findingsmentioning
confidence: 99%
“…Similarly, a recent study based on information in the National Cancer Database found that Black individuals residing in neighborhoods with the highest socioeconomic status are more likely than White individuals residing in neighborhoods with the lowest socioeconomic status to be diagnosed with advanced‐stage lung cancer 106 . Even for childhood cancer, Black children are 24% more likely to be diagnosed with distant‐stage disease than White children, regardless of family insurance status 107 …”
Section: Selected Findingsmentioning
confidence: 98%
“…106 Even for childhood cancer, Black children are 24% more likely to be diagnosed with distant-stage disease than White children, regardless of family insurance status. 107 Racial disparities in cancer occurrence and outcomes are largely the result of longstanding inequalities in wealth that lead to differences in both risk factor exposures and access to equitable cancer prevention, early detection, and treatment. 108,109 Ultimately, disproportionate wealth stems from hundreds of years of structural racism, including segregationist and discriminatory policies in criminal justice, housing, education, and employment that have altered the balance of prosperity, security, and other social determinants of health.…”
Section: Cancer Disparities By Race and Ethnicitymentioning
confidence: 99%
“…For example, Black and Asian Pacific Islander children have lower incidence rates of most major tumor types compared to non‐Hispanic White children, while Hispanic children have notably higher incidence rates of ALL, retinoblastoma, and hepatoblastoma 24 . Additionally, non‐Hispanic Black, Asian, and Hispanic children are more likely to present with advanced stage cancer than non‐Hispanic White children, 25 and may have higher rates of molecular subtypes that confer a poor prognosis 26 . Compared with non‐Hispanic White children, non‐Hispanic Black and Hispanic children experience lower survival from many cancers, including leukemias, 27 lymphomas, 28 central nervous system (CNS) tumors, 29 and non‐CNS solid tumors 30 .…”
Section: Strategic Planmentioning
confidence: 99%